Theoretical and methodological foundations for the study of the civilization essence - Bauyrzhan M., Bozhbanbaev; Rauan A. , Kemerbay (BULLETIN of the L.N. Gumilyov Eurasian National University. Historical sciences. Philosophy. Religion Series, 2023)
To date, in the history of mankind, many types and theories of civilization have been formed, opposite to each other, irreconcilable, sometimes even hostile. At first glance, different types and theories of civilizations that are opposites to each other create the basis for friction and struggle. However, in our opinion, the variety of types and theories of civilizations does not interfere with the development and prosperity of civilizations, since these theories study the essence of civilization from different points of view, more deeply and comprehensively. In fact, what seems at first glance wrong and impossible with a more detailed and comprehensive analysis turns out not to be so. So, the type of civilization is primarily a scientific concept that includes the stages of development of society, society, ethnos, etc., while an important role in the formation of civilization is played by the commonality of the formation of cultural, economic, historical, social, demographic, etc. components, common foundations and values of spiritual life associated with the development of culture, its potential for further development.